Examining Parental Expectations and Fault Attributions for Child Sexual Abuse - Zagrodney, Jessica L. (Journal of interpersonal violence, 2021)
Previous research has demonstrated that nonoffending mothers are held at fault when their child is sexually abused and this fault is directly linked to a decrease in help-seeking behavior. It is unclear, however, whether similar fault is applied to nonoffending fathers, as little such research on fathers exists. What does exist is marked by methodological limitations. Using an experimental vignette design, 154 participants were randomly assigned to read one of two hypothetical abuse scenarios (i.e., nonoffending mother or nonoffending father) depicting the sexual abuse of a female child by an adult male perpetrator. Participants rated levels of fault attributions assigned to either parent and then provided open-ended responses outlining their reasons for their attribution ratings. Quantitatively, both mothers and fathers were assigned similar amounts of fault for the sexual abuse. Thematic analysis of participants’ justifications for their assigned fault attributions revealed both mothers and fathers are subject to similar expectations that either increase or decrease assigned fault, with the exception of one theme, Disbursement, in which participants distributed fault away from fathers toward others (e.g., the nonoffending mother). By understanding parent blaming and the reasons behind parent blaming attributions, future research can work to improve these attitudes.